Stratification of Latent Mycobacterium tuberculosis Infection by Cellular Immune Profiling. (28th February 2017) - Halliday, Alice; Whitworth, Hilary; Kottoor, Sherine Hermagild; Niazi, Umar; Menzies, Sarah; Kunst, Heinke; Bremang, Samuel; Badhan, Amarjit; Beverley, Peter; Kon, Onn Min; Lalvani, Ajit
Abstract : Persons with latent Mycobacterium tuberculosis infection (LTBI) vary by their risk of progression to tuberculosis but are clinically indistinguishable. We identified a cellular immune signature that correlates strongly with time since exposure, providing a rationale for immunological risk stratification to improve targeting of LTBI treatment. Abstract: Background: Recently acquired and remotely acquired latent Mycobacterium tuberculosis infection (LTBI) are clinically indistinguishable, yet recent acquisition of infection is the greatest risk factor for progression to tuberculosis in immunocompetent individuals. We aimed to evaluate the ability of cellular immune signatures that differ between active tuberculosis and LTBI to distinguish recently from remotely acquired LTBI. Methods: Fifty-nine individuals were recruited: 20 had active tuberculosis, 19 had recently acquired LTBI, and 20 had remotely acquired LTBI. The proportion of mycobacteria-specific CD4 + T cells secreting tumor necrosis factor α (TNF-α) but not interferon γ or interleukin 2 which had a differentiated effector phenotype (TNF-α–only TEFF ), and the level of CD27 expression on IFN-γ–producing CD4 + T cells, were detected by flow cytometry. Results: The TNF-α–only TEFF signature was significantly higher in the group with recently acquired LTBI, compared with the group with remotely acquired LTBI ( P < .0001), and it discriminated between these groups with high sensitivity and specificity, with an area under the curve of 0.87. Two signatures incorporating CD27 expression did not distinguish between recently and remotely acquired LTBI. Interestingly, the TNF-α–only TEFF signature in participants with recently acquired LTBI was more similar to that in participants with tuberculosis than that in participants with remotely acquired LTBI, suggesting that recently acquired LTBI is immunologically more similar to tuberculosis than remotely acquired LTBI. Conclusions: These findings reveal marked biological heterogeneity underlying the clinically homogeneous phenotype of LTBI, providing a rationale for immunological risk stratification to improve targeting of LTBI treatment.